The Impact of the European Union Emissions Trading Scheme on Competitiveness in Europe - Ulrich Oberndorfer; Klaus Rennings (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
This literature review analyses the impacts of the EU ETS on competitiveness focussing on existing simulation studies. We have identified the choice of the reference scenario as the most critical issue for an appropriate analysis of the relevant literature. We find, however, that effects of the scheme on competitiveness are modest, even given the business as usual case that does not take the legally binding framework of the Kyoto Protocol into account. Furthermore, the impacts of the EU ETS are smaller than the impacts of alternative Kyoto-based regulation scenarios. Compared to these other regulation methods ETSs can have positive competitiveness effects. However, the EU ETS is not designed to boost Europe?s economy. Its prime purpose and justification is to ensure that Europe?s CO2 emissions are brought down and Kyoto targets are reached at minimal costs. To our opinion, it is therefore important that the system as well as modifications to it do not undermine the environmental goals associated with this policy instrument.
Keywords: Q21; Q28; Q43; 330; emissions trading; competitiveness; environmental regulation